A study to assess the newborn care practices among mothers at a tertiary care hospital in Hyderabad, Telangana - Pulla, Anupama; ., Asma; Thomas, Vimala (International Journal Of Community Medicine And Public Health, 2019)
Background: Early neonatal period (<1 week) is the crucial period in the life of an infant as the risk of death is greatest during the first 24- 48 hours after birth. In India, around 61.3% of all infant deaths occur during neonatal period (<28 days) and more than half of these deaths occur during early neonatal period. Most of these deaths can be attributed to harmful newborn care practices in relation to bathing, feeding, cord care etc. The aims and objectives of the study were to assess the newborn care practices among women who delivered in Gandhi Hospital; to assess the relationship between maternal education and newborn care practices among study population. Methods: A cross sectional study was carried out among 200 women who delivered in Gandhi Hospital, Hyderabad, Telangana from March to June 2017 and a predesigned, pre tested questionnaire was used to obtain information. Results: The mean age of study population was 21.5±2.3 years. Around 61.9% of mother’s breastfed within first hour of life and 93.5% fed colostrum. Around 17% were given pre lacteal feeds like cow milk, honey, water etc. No harmful cord care practices like application of cow dung etc. were not followed. Conclusions: Majority of the study population had correct knowledge regarding newborn care practices. Although some of the traditional practices were still observed like giving pre lacteal feeds, discarding colostrum and avoidance of certain foods like pulses, meat, curd etc. by mother.